Urgent Regulation: Integrating the SDGs into the PTKN Strategic Plan is Key to Accelerating Global Participation in the Times Higher Education Impact Rankings - I Gede Krisna Putra (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This Police Paper analyzes the participation of State Religious Universities (PTKN) in THE Impact Rankings. The components that must be included in this abstract are: First, Background and Focus of the Problem: The low participation of State Religious Universities (PTKN) in THE Impact Rankings of SDGs-based global performance indicators is a crucial issue that obscures PTKN's contribution to sustainable development. This problem is rooted in the absence of SDGs in PTKN's strategic planning (Renstra), which is exacerbated by the absence of contextual technical regulations and operational guidelines. The absence of this policy instrument makes it difficult for institutional planners to translate SDG objectives into work programs, indicators, and performance reporting that are in accordance with global standards. Second, the methodology of this paper uses a qualitative-descriptive policy analysis approach. Data were collected through in-depth literature studies (desk research) of PTKN planning documents, Ministerial Regulations, Ministerial Decrees, and official reports and methodologies of THE Impact Rankings. Problem analysis was identified and prioritized using the USG method (Urgency, Seriousness, Growth). Policy alternatives are formulated in the form of regulations, then comprehensively evaluated using William N. Dunn's criteria (Effectiveness, Efficiency, Adequacy, Responsiveness) to determine the priority of recommendations. Third, Key Findings and Recommendations: The USG analysis confirmed that strategic planning issues are a top priority (Score 19). Dunn's evaluation indicates that the most effective and efficient solution is intervention at the basic regulatory level. Based on these findings, the main policy recommendation is the issuance of a Ministerial Decree (KMA) on the Integration of SDGs into the PTKN Strategic Plan. This regulation will provide an explicit and systematic legal mandate, shifting the institution's orientation from administrative performance to impact-based, while also serving as a foundation for technical reporting guidelines. This step is expected to overcome structural barriers and increase PTKN's participation in the global arena.